Imbalance of vasoconstrictor / vasodilation potential caused by experimental osteoarthritis development - Savуtskyі, I. V.; Orel, K. S.; Levkivska, O. S. (Journal of Education, Health and Sport, 2018)
Study have been carried out on white Wistar line rats (age – 3 months, weight – 180-220 g). According to the tasks the animals were divided into 7 groups: 1st group is intact (n = 20). 2nd group is rats, which were modeled osteoarthritis without further correction and were withdrawn from the experiment in the first stage (7th day) (n=40). 3rd group is rats, which were modeled osteoarthritis without further correction and removed from the experiment in the second stage (21st day) (n=40). 4th group is rats, in which experimental osteoarthritis was corrected with nonsteroidal anti-inflammatory drugs (NSAIDs) (Diclofenac) and aminoguanidine and removed from the experiment in the first stage (7th day) (n=20). 5th group is rats, in which experimental osteoarthritis was corrected with NSAIDs (Diclofenac) and aminoguanidine and withdrawn from the experiment in the second stage (21st day) (n=20). 6th group is rats, where experimental osteoarthritis was corrected using NSAIDs and a 7% L-arginine solution and withdrawn from the experiment in the first stage (7th day) (n=20). 7th group is rats, in which experimental osteoarthritis was corrected with NSAIDs and 7% L-arginine solution and withdrawn from the experiment in the second stage (21st day) (n=20) Animals were withdrawn from the experiment for the 7th day and the 21st day after the simulation of the pathological condition. NSAIDs (Diclofenac), aminoguanidine and L-arginine were administered from the beginning of the study. As a research result was found significant increase in the endothelin-1 level in the blood, which indicates about imbalance endothelium functioning in the predominance direction of vasoconstrictor potential. Shift the balance towards vasoconstriction is evidence of the blood vessels vasodilating potential weakening. There is a positive trend in the endothelial dysfunction correction in osteoarthritis with the aminoguadine administration. L-arginine effectiveness has been proven as a corrective agent for the endothelial function normalization in experimental osteoarthritis. It has been proven that use of nitric oxide donor are more effective than the use of an inducible NO synthase inhibitor.